2003
DOI: 10.1046/j.1538-7836.2003.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Inaccuracy of international normalized ratio (INR) measurements and suggestions for improved WHO guidelines for calibration of reference preparations – a statistical study

Abstract: Summary. Numerous empirical studies show that the accuracy of international normalized ratio (INR) measurements is unsatisfactory and worse than generally expected. We demonstrate that a plausible reason for this large inaccuracy is a conventional calibration procedure of reference preparations with (i) an erroneous assumption that the line relating logarithmic prothrombin times (log PTs) of patients passes through the mean log PT of the 'normal' population (mean normal PT); (ii) non-perceived interactions bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…All instruments used in this study were calibrated against an IRP or methods traceable to an IRP in accordance with WHO guidelines (2 ). However, it has been shown that the calibration procedure does not necessarily harmonize with the INR results (3,5 ). Differences in calibration were taken into account by correction of all results by use of linear regression.…”
Section: Systematic Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…All instruments used in this study were calibrated against an IRP or methods traceable to an IRP in accordance with WHO guidelines (2 ). However, it has been shown that the calibration procedure does not necessarily harmonize with the INR results (3,5 ). Differences in calibration were taken into account by correction of all results by use of linear regression.…”
Section: Systematic Differencesmentioning
confidence: 99%
“…Agreement in results between laboratory INR instruments and methods improved after the introduction of WHO guidelines that launched new calibration procedures (2 ). Nevertheless, harmonization of results from different laboratories remains challenging (3)(4)(5). Different types and sensitivities of thromboplastins (2 ) and interactions between thromboplastin and coagulation factors of individual patients may influence the accuracy of the instruments (4,6,7 ).…”
mentioning
confidence: 99%
“…the use of a sensitive tromboplastin, method for clot detection, full-blood versus plasma analysis, precision and method used for the calibration process, and the stability of the patients OAT [45][46][47][48]. INR determined in the laboratory using a standardized and quality controlled method (with internal and external quality assurance) is often referred to as the golden standard [49], to which all other methods should be compared.…”
Section: Measurement Of Inrmentioning
confidence: 99%
“…Variations between various thromboplastin preparations have in the past led to decreased accuracy of INR readings, and a study suggested that despite international calibration efforts (by INR) there were still statistically significant differences between various kits [6]. Harmonization of results from different laboratories remains challenging [7]. Different types and sensitivities of thromboplastins [5] and interactions between thromboplastins and coagulation factors of individual patients may influence the accuracy of the instruments [8][9][10].…”
Section: Introductionmentioning
confidence: 99%